Smart system of ultrasonic car parking - Mahmad Tabib, Mahmad Tajudin (2008)
With the development of automobile industry, the number of private cars is greatly increasing. Correspondingly, the number of rookie drivers is increasing as well. For the rookie drivers, how to backing is always a troublesome operation. Many of them complained that their valuable cars are easily got damaged by obstacles that are hardly seen through their rearview mirror. So in this project, a new type system has been designed: smart system of ultrasonic car parking with different display mode, audio mode and smart mode: i.Liquid crystal display (LCD) display modes: Used to display the zone of your car based on condition that have been set. ii.LED display modes: Ordinary display modes. 6 LEDs are used to display the distance of obstacles. The more LEDs are lightening, the closer obstacles are. iii.A buzzer or a beeper which is a signaling device is used to show the distance of the car with the obstacles behind it. The faster tone of the beep of buzzer means the distance of obstacles and car are closer. iv.Smart mode: The engine will automatically stop if the car is in stop zone which mean it is dangerous condition to parking the car.